2018
DOI: 10.1186/s13028-018-0392-6
|View full text |Cite|
|
Sign up to set email alerts
|

Canine breeds associated with gastric carcinoma, metaplasia and dysplasia diagnosed by histopathology of endoscopic biopsy samples

Abstract: BackgroundGastric carcinoma (GC) is a rather rare pathological finding in dogs, with the exception of some breeds which seem predisposed. The etiopathogenesis is largely unknown in dogs, whereas in humans GC often develops from gastric mucosal metaplasia and dysplasia. This study investigates whether dogs of certain breeds are more often subject to gastroduodenoscopy (GDS), and diagnosed with GC, mucosal metaplasia or dysplasia. A retrospective clinical database search was performed at the Veterinary Teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
4
0
2
Order By: Relevance
“…Moreover, 6/27 (22%) BSD over 5.5 years of age were diagnosed with GC regardless of clinical condition. This further corroborates a marked predisposition to GC in these ageing Tervuren and Groenendael BSD, as GC is rare in dogs, except for a few predisposed breeds [ 1 , 6 ]. Even more importantly, it shows that gastric pathology including GC can occur as an occult disease in affected dogs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, 6/27 (22%) BSD over 5.5 years of age were diagnosed with GC regardless of clinical condition. This further corroborates a marked predisposition to GC in these ageing Tervuren and Groenendael BSD, as GC is rare in dogs, except for a few predisposed breeds [ 1 , 6 ]. Even more importantly, it shows that gastric pathology including GC can occur as an occult disease in affected dogs.…”
Section: Discussionsupporting
confidence: 70%
“…GC is frequently seen in Tervuren and Groenendael Belgian Shepherd dogs (BSD) and some other dog breeds, including Bouvier des Flandres, Collie, Standard Poodle, Norwegian Elkhound and Chow-Chow [ 1 – 5 ]. A previous study in Finland found an increased risk ratio (RR = 19) for Tervuren BSD undergoing endoscopy to be diagnosed with GC [ 6 ]. In the majority of cases, GC carries a very poor prognosis, since diagnosis is mostly achieved at a late, advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are derived from a relatively homogenous population of dogs, mainly consisting of middle-aged Belgian shepherds. Belgian shepherds are predisposed to gastric carcinoma (Candido et al, 2018); which is the reason why these dogs were the main breed undergoing gastroduodenoscopy. It is also the reason why symptomatic and asymptomatic dogs with a genetic neoplastic predisposition were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinomas gástricos são neoplasias malignas de origem epitelial, classificados de acordo com as características histológicas em papilar, tubular, mucinoso e pouco coeso (Galvão et al, 2009;Munday et al, 2017). Nos caninos os adenocarcinomas representam a neoplasia gástrica primária mais comum (Gualtieri et al, 1999;Willard, 2012;Candido et al, 2018), acometendo com maior frequência machos com mais de 10 anos de idade e das raças Rough Collie, Staffordshire Bull Terrier, Chow-chow, Pastor Belga, Lundehund Noruegues, Cairn Terrier e Terrier Branco de West Highland (Sullivan et al, 1987;Bilek et al, 2007;Seim-Wikse et al, 2013;Munday et al, 2017;Koterbay et al, 2020;Hardas et al, 2021).…”
Section: Introductionunclassified
“…Os sinais clínicos de tumor gástrico são inespecíficos como inapetência, vômito intermitente ou crônico e perda de peso progressiva com o diagnóstico na maioria dos casos determinado somente em estágio avançado da doença (Sullivan et al, 1987;Von Babo et al, 2012;Seim-Wikse et al, 2013;Abrams et al, 2019), sendo esses sinais clínicos observados mais tardiamente na variante mucinosa (Galvão et al, 2009;Munday et al, 2017). A etiologia dos carcinomas gástricos é desconhecida na maioria dos casos, porém pode estar associada a fatores ambientais e genéticos, assim como em humanos (Scanziani et al, 1991;Lubbes et al, 2009;Munday et al, 2012;Seim-Wikse et al, 2013;Hugen et al, 2016;Munday et al, 2017;Candido et al, 2018). Histologicamente o adenocarcinoma mucinoso é caracterizado por células neoplásicas contendo mucina no citoplasma com núcleo deslocado para a periferia (célula em anel de sinete), além de mucina extracelular (Munday et al, 2017;Hardas et al, 2021).…”
Section: Introductionunclassified